1981
DOI: 10.1161/01.res.49.4.877
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of coronary velocity and reactive hyperemia in the coronary circulation of humans.

Abstract: An acceptable method for measuring phasic coronary velocity and reactive hyperemia in humans has not been available. We have developed a doppler probe which can be coupled to surface coronary vessel* at the time of cardiac surgery with a small suction cup. Phasic coronary velocity can be measured with a signal to noise ratio that exceeds 20:1. Animal studies have shown that the probe does not alter myocardial perfusion or cause tissue damage. In addition, changes in mean coronary velocity are closely related (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
1
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(60 citation statements)
references
References 22 publications
1
57
1
1
Order By: Relevance
“…Changes in mean coronary blood velocity are directly correlated with changes in coronary blood flow. 21 Data are presented as meanϮSEM. The changes in hemodynamic and wall thickening data produced by BK administration in the partial and complete occlusion groups were analyzed by two-way repeated-measures ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in mean coronary blood velocity are directly correlated with changes in coronary blood flow. 21 Data are presented as meanϮSEM. The changes in hemodynamic and wall thickening data produced by BK administration in the partial and complete occlusion groups were analyzed by two-way repeated-measures ANOVA.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary flow reserve has been estimated in man during surgery (Marcus et al, 1981), in the cardiac catheterization laboratory (White et al, 1984;Wilson et al, 1985), and most recently in the echocardiography laboratory (Saraste et al, 2001;Voci et al, 2004) using the ratio of hyperemic to baseline flow velocity. The reported values are between 2.5 and 5.0 depending on the flow or velocity sensing method, the vasodilator, and the experimental or clinical conditions.…”
Section: H/b In Mice Versus Manmentioning
confidence: 99%
“…Higher H/B in Old mice-In man H/B is used to estimate the severity and significance of several cardiac pathologies including coronary artery disease which reduces hyperemic flow (Gould et al, 1974;Marcus et al, 1981;Marcus, 1983), and valvular disease which increases resting cardiac work and baseline flow (Marcus et al, 1982). Wieneke, et al (2006) studied several factors which might influence H/B in man and found that only age and baseline velocity influenced H/B in healthy individuals.…”
Section: H/b In Mice Versus Manmentioning
confidence: 99%
See 2 more Smart Citations